Assessing Gen Y impact on organizational performance: an analysis from top management perspective / Fadilah Puteh, Maniam Kaliannan and Nafis Alam - Puteh, Fadilah; Kaliannan, Maniam; Alam, Nafis (Faculty of Administrative Science and Policy Studies, 2015)
This paper examines Generation Y (Gen Y) as today’s most influential and powerful workforce and its impact on organizational performance (OP) from the perspective of the top management. The unique characteristics of Gen Y combined with its strong bargaining power have changed the approach organizations manage their manpower as well as the entire management landscape. Being the demanding and dynamic workforce, however, less is known on how Gen Y affects OP. Qualitative approach is employed to delve into this issue. As a key driver in Human Resource Management (HRM), top management views are imperative to understand the impact of Gen Y on OP. Fifteen HR Directors and Managers from Malaysian service-based industries were invited to participate in this study. Their views are audiotaped, transcribed, and analysed using thematic analysis. Results indicate several emerging themes with respect to Gen Y and OP. This study reveals intriguing findings on how top management views Gen Y and its impact on OP. It is envisaged that the findings of the study will contribute to the existing body of knowledge in the field of Human Resource Management and Human Resource Development.